Analysis for educational purposes of the movie Drumline: the musical rhythm as a tool of cohesion (Foro de Educacion, 2013)
This study aims to encourage reflection on the benefits of the music classroom of high school, through the analysis of the movie «Drumline». To carry out this purpose, a theoretical framework about how to analyze films is built, showing different studies on the use of this tool in education and ending with research where that instrument is deployed in the music classroom. The analysis of the movie «Drumline» have been made from a plot standpoint, and the categories established have been linked to different aspects of educational content to the curriculum of high school. These categories are presented with corresponding timelines, under the intention to be used by educators in the teaching-learning process. Thus, through categories different aspects of the curriculum are worked, from an interdisciplinary and cross curricular aspect.